Prospective study on clinical outcomes of lichtensteins tension free inguinal hernioplasty under local anaesthesia - Brar, Navjot Singh; Bajwa, Rajbir Singh (International Surgery Journal, 2017)
Background: Hernia may be generally defined as a protrusion of viscus or part of a viscus though an abnormal opening in the walls of its containing cavity. The Greek word ‘hernia’ means an offshoot, a budding or bulge. But the Latin word ‘hernia’ means a rupture or tear. The most important principle in reconstruction surgery is to avoid tension when restoring the muscular or elastic structures. The modern biologically based concept for repair of groin hernia, acquired during adult life, is application of a patch, avoidance of tension and use of local, spinal or epidermal anaesthesia. Methods: Present study is a Prospective study conducted in the Department of General Surgery in Sri Guru Ramdas Medical College and Hospital. Patients admitted in wards with inguinal hernia from General Surgery out-patient Department were selected for study. The study consisted of 60 patients between 15 to 74 years; The study period is from April 2015 to September 2016. The main aim and objective of any hernia repair is to avoid any recurrence and also acceptability to the patient in terms of pain, discomfort, other complications during follow up and obviously in terms of cost- effectiveness of repair. Results: The present study comprises 60 cases of inguinal hernia who were admitted in the wards of Department of General Surgery in the Sri Guru Ramdas Institute of Medical sciences and research. The study was carried out during span of 1½ years. All of these cases were studied prospectively and results were analysed from various angles. Among total 60 cases in this study, maximum cases belonged to age group 35-44 years ;15 (25%) and minimum to age group 65-74 years 5 (8.3%). Case distribution as per type of hernia, it was observed that among total 60 cases 34 (56.67%)had inguinal hernia and rest 26 (43.3%) had inguino scrotal hernia. Most 0f the cases had right sided hernia 35 (58.33%), left sided hernia was seen only in 23 cases (38.33%) whereas bilateral hernia was present in 2 (3.33%). Conclusions: From our results of observations in the study we can conclude that-The methods of Lichtenstein’s tension free inguinal hernioplasty under local anaesthesia is safe, simple, effective, economical, and without any side effects such as hypotension, nausea, vomiting, urinary retention, and spinal headache.